1986
DOI: 10.1080/00288233.1986.10423489
|View full text |Cite
|
Sign up to set email alerts
|

Variation in partitioning and percentage nitrogen and phosphorus content of the leaf, stolon, and root of white clover genotypes

Abstract: As part of a programme to breed a productive white clover (Trifolium repens L.) tolerant of low soil phosphorus (P) levels, 98 white clover and 2 Lotus pedunculatus Cav. genotypes were examined for partitioning of P, nitrogen (N), and dry matter within the plant, and for concentration of P and N within leaves, stolons, and roots. Genotypes were grown in pots with either 300 or 2000 mg P per kg soil. Differences among genotypes for 0,10 P content and partitioning of P within the plant did not result in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Twenty genotypes were collected from a range of soils on roadside cuttings in the North Island; 30 genotypes were from five cultivars (Kent Wild White, Kopu, Huia, S.100, and Regal)(6 genotypes from each cultivar); and 48 genotypes were from an extensive collection of hill country white clovers (Suckling and Forde, 1978). A full description of genotypes is given by Caradus (1986). Genotypes were initially grown in potting mix until sufficient stolon tips were generated to allow vegetative propagation.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty genotypes were collected from a range of soils on roadside cuttings in the North Island; 30 genotypes were from five cultivars (Kent Wild White, Kopu, Huia, S.100, and Regal)(6 genotypes from each cultivar); and 48 genotypes were from an extensive collection of hill country white clovers (Suckling and Forde, 1978). A full description of genotypes is given by Caradus (1986). Genotypes were initially grown in potting mix until sufficient stolon tips were generated to allow vegetative propagation.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Additionally, correlation analyses were used to identify characters that vary together since when selecting for a trait it is important to be aware of associated characters that may similarly change in response to selection. This paper is the second in a series which firstly, examined (i) the extent of variation for %P, %N and partitioning of N, P and dry matter to plant components, (ii) the effect of P supply on these characters, and (iii) the effect on these characters of selection for white clover plants able to tolerate grazing in low soil P conditions (Caradus, 1986), and secondly, in this paper, examines (iv) the heritability of %P, %N and partitioning of N and P to plant components, (v) the effect of P supply on heritability estimates and (vi) relationships between plant characters and the consequences of selection for high and low %P.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these correlations were only moderate (Table 4) so that it may be possible, if required, to select against these trends, such that high-yielding, high P-responsive genotypes could be obtained with either high or low % P since the correlation between leaf % P and P response coefficients was not significant (Table 4). Leaf size and proportion of leaf were not correlated (Table 4), as has been observed in other studies (Caradus 1986).…”
Section: Comparison Of High and Low Phosphorus Response Groupsmentioning
confidence: 47%
“…plant's N fixation or N status in addition to P. In fact, in lucerne, selections for high % P did not differ in response to added P from control populations (Miller et al 1987). Although large differences were found among white clover genotypes grown at two P levels for % P levels in leaf, stolon, and root, and partitioning of P within the plant, these did not result in differences in DM response to P (Caradus 1986). Similarly, Spencer et al (1980) found differences between eight lines of white clover for shoot %P but this was not translated into P response differences.…”
Section: Comparison Of High and Low Phosphorus Response Groupsmentioning
confidence: 77%
See 1 more Smart Citation